FACTORS INFLUENCING INNOVATIVE ACTIVITY OF TRANSPORT ENTERPRISES - BONIAR, Svitlana; PAKHOLKA, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the article is to study the set of exogenous and endogenous factors that determine the possibility of introduction and efficiency of innovation in transport enterprises, and the development of indicators to evaluate the impact of these factors. It is proved that in the context of modern challenges, namely armed conflict, macroeconomic instability, strengthening of environmental and social requirements, the strategic importance of implementing innovative solutions, which are tools for improving the adaptability, sustainability and efficiency of transport enterprises, is increasing. Four main areas of innovation in the transport industry have been identified and detailed, namely: technical and technological innovations, environmental innovations, management and organizational innovations, financial and investment innovations. It is substantiated that it is advisable to consider the set of exogenous and endogenous factors for the analysis of innovative activity of transport enterprises. The set of exogenous factors includes geopolitical and macroeconomic factors, regulatory environment, technical and technological progress, global environmental trends, social requests and consumer behavior. The set of endogenous factors includes organizational features and management characteristics, personnel potential, material and technical base, financial capacity. For each group of exogenous and endogenous factors, a set of quantitative and qualitative indicators that characterize their impact on the innovative development of transport enterprises is proposed, which will allow to form a comprehensive system of assessing the level of innovative activity of enterprises. It is emphasized that such indicators can be adapted for internal audit, monitoring of innovative processes and detecting narrow places.